MANAGEMENT OF VASCULAR WILT OF LENTIL THROUGH OILS - KUMAR, VIJAY; GARKOTI , ANKITA; H. S. TRIPATHI (The Bioscan, 2014)
Field experiments were carried out in N. E. Borlaug Crop Research Center of G. B. Pant University of Agriculture and Technology, Pantnagar during Rabi season 2007-08 and 2008-09 crop season. It has been observed that seed treatment with menthol oil (50ml/kg seed) showed significant response with respect to disease incidence (0.56% and 1.32%), 1000-grain weight (13.73g and 13.67g) and grain yield (603.10 and 503.50) kg/h followed by geranium oil (50 ml/kg seed) showed disease incidence (0.82% and 1.51%),1000 grain weight (13.38 g and 13.03g), grain yield (584.50 and 475.20) Kg/ha and citronella oil (50ml/kg seed) resulted disease incidence (1.03% and 2.15%),1000 grain weight (12.53g and 12.50g), grain yield (517.30 and 465.00) kg/ha while Jatropha oil (50ml/kg seed) showed high disease incidence(1.42% and 3.42%),1000 grain weight (11.80g and12.03g), lowest grain yield. (425.00 and 392.70) Kg/ha during 2007-08 and 2008-09 crop season respectively. Minimum disease incidence and maximum grain yield recorded in menthol oil treated plots followed by geranium oil and citronella oil while Jatropha oil showed high disease incidence and lowest grain yield during both crop season 2007-08 and 2008-09.